PERUSAHAAN PENGELOLA LIMBAH BAHAN BERBAHAYA & BERACUN (B3) CIPTAKAN KOMUNIKASI PERSUASIF GREEN MARKETING MELALUI PERSONAL SELLING - Nurhaliza, Siti; Pinariya, Janette Maria (Universitas Swadaya Gunung Jati, 2024)
Waste management is essential for environmental sustainability and public health. Handling hazardous and toxic waste (B3) is part of this process. B3 waste with its characteristics (infectious, corrosive, liquids and flammable solids as well as others). If this material is not handled or disposed of properly, it can harm the environment and human health. Company B3 waste management must be carried out effectively by companies that produce waste from their activities. Green Marketing is a strategy to prioritize the market for environmentally friendly products to meet customer demands and preferences (Nugrahaa et al., 2024). In these marketing activities, persuasion in personal selling is essential in promoting and retaining consumers and maintaining good relationships with business clients involved in waste management. The two fundamental theories are the idea of face-to-face selling and the message theory of persuasive communication (authority, credibility, and attractiveness). The qualitative descriptive methodology used in this research involves conducting interviews to collect data. In green marketing, businesses need to create attractive communications to increase persuasion. The seven steps of Personal Selling (Prospect and Qualification, Pre-approach, Approach, Presentation, Demonstration, Objection Handling, Closing, and Follow-up) are communication ideas used to offer B2B products and services. This research found that customers considered green marketing efforts in waste management marketing when deciding to cooperate and continue using PT TSA services. Keywords: Green Marketing, SDGs, Hazardous and Toxic Waste, Persuasive Communication, Personal Selling